On the worldsheet derivation of large N dualities for the superstring - Berkovits, N.; Ooguri, H.; Vafa, C. (Springer, 2004)
Large N topological string dualities have led to a class of proposed open/ closed dualities for superstrings. In the topological string context, the worldsheet derivation of these dualities has already been given. In this paper we take the first step in deriving the full ten-dimensional superstring dualities by showing how the dualities arise on the superstring worldsheet at the level of F terms. As part of this derivation, we show for F-term computations that the hybrid formalism for the superstring is equivalent to a (c) over cap = 5 topological string in ten-dimensional spacetime. Using the (c) over cap = 5 description, we then show that the D brane boundary state for the ten-dimensional open superstring naturally emerges on the worldsheet of the closed superstring dual.